Long-term outcome of the cheek advancement flap, a report of 41 cases. Issue 6 (1st November 2016) - van Onna, Martijn A.; Haj, Mona; Smit, Jeroen M.; Hoogbergen, Maarten M.
Abstract: Background: Due to incidental occurrence of ectropion as a late complication of cheek advancement flaps, this study investigated the long-term effects of these flaps for post-Mohs' reconstruction of the cheek aesthetic. Methods: All the patients who underwent a cheek advancement flap in the Catharina Hospital Eindhoven between January 2006 and January 2013 where included and assessed by means of a retrospective chart review and a survey about the long-term outcome and patient satisfaction. Results: A retrospective chart review was performed on all 54 eligible patients, and 41 (76%) of these patients participated in the study. The mean follow-up was 3.5 years (SD = 2.0, range = 1–7 years). Early complications were ectropion (6%), infection (2%), dog-ears (1%), haematoma (4%), and distal tip necrosis (2%). Late outcome and complications were sensory neuropathies (41%), late ectropion (7%), hypopigmentation of scars (29%), contractures (27%), and abnormal hair distribution (17%). Patients rated their reconstruction as good or excellent in 87% of cases. Conclusions: The cheek advancement flap is a suitable technique for reconstruction of large cheek skin defects after excision of skin malignancies. However, patients should be informed that long-term complications, including ectropion, can occur. Additional follow-up might lead to an early detection of these late effects.